RELEVANSI FEMINISME DALAM ISU KONTEMPORER: KEHADIRAN UN WOMEN DALAM PEMBERDAYAAN PEREMPUAN DAN MANUSIA DI AFGHANISTAN - Zhafir, Ali Zhafir Talmullah; Nurmasari Situmeang; Asep Kamaluddin Nasir (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
Abstract Feminism is still an important issue in international relations. Especially in the field of non-traditional security. The issue of women's role in life is still being fought today. These include discrimination against women and criminal issues such as human trafficking and exploitation of women. Another issue that needs special attention is the limited involvement of women in building the country. One country that is still of particular concern to the role of women is Afghanistan. For some countries, Afghanistan has rules that do not support the roles of women so that the struggle for the development of human resources, especially women in Afghanistan, is still ongoing. UN Women is present in the country to empower women and humans in Afghanistan to encourage the role of women in building their nation. The framework of this paper uses feminism to describe the phenomenon that occurred in the country and see its relevance to current issues. In fact, there are still many things that threaten human life, especially women, which should be the focus for UN Women to solve these problems. Keywords: Feminism, Non-Traditional Security, UN Women Abstrak Feminisme masih menjadi isu penting dalam hubungan internasional. Terutama di bidang keamanan non-tradisional. Permasalahan peran perempuan dalam berkehidupan masih diperjuangkan hingga kini. Masalah itu mencakup diskriminasi terhadap kaum perempuan dan masalah kriminal seperti perdagangan manusia serta eksploitasi perempuan. Masalah lain yang perlu menjadi perhatian khusus yaitu keterbatasan keterlibatan perempuan dalam membangun negara. Salah satu negara yang masih menjadi perhatian khusus terhadap peran perempuan yaitu Afghanistan. Bagi beberapa negara, Afghanistan memiliki aturan yang kurang mendukung peran-peran perempuan sehingga perjuangan untuk perkembangan sumber daya manusia khususnya perempuan di Afghanistan masih terus dijalankan. UN Women hadir di negara tersebut untuk melakukan pemberdayaan perempuan dan manusia di Afghanistan guna mendorong peran perempuan dalam membangun bangsanya. Kerangka berpikir tulisan ini menggunakan feminisme untuk menggambarkan fenomena yang terjadi di negara tersebut serta melihat relevansinya terhadap isu yang berkembang saat ini. Nyatanya, masih banyak hal yang mengancam kehidupan manusia khususnya perempuan yang harus menjadi fokus bagi UN Women untuk menyelesaikan masalah tersebut. Kata Kunci: Feminisme, Keamanan Non-Tradisional, UN Women